STRATEGI MENINGKATKAN KUALITAS OLAH BAHASA UNTUK CERITA PENDEK SISWA SEKOLAH DASAR DENGAN PENDEKATAN GENRE-BASED - Djatmika, Djatmika; Primasita, Fitria Akhmerti; Priyanto, Agus Dwi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Indonesian elementary school students show their motivation to write. A kind of books written by and for children of their age, commonly termed as Kecil-Kecil Punya Karya (KKPK) ‘although young we have writing works’, are nowdays available at bookstores. These books can further motivate other children to compose. To accommodate this motivation, the language center of Sebelas Maret University of Surakarta held a writing contest for elementary school students in Surakarta and the surrounding area. Thirtyfour students participated the contest, thus 34 texts from such a competition were collected as the object of analysis in this study to see the quality of the text structure as well as the text texture of the texts. The analysis on the text structure shows that several texts are arranged in a single kind of genre. However, the other texts are composed in multi-genre—meaning that each text in this kind demonstrates the features of a genre, but it accomodates other short texts with different genre. The former is named as a text with a macro genre, whereas the latter are termed as texts with a micro one. Meanwhile, the choice of words and the exploitatio of grammatical construction for the clauses of most of the texts shows weaknesses. Many academic and technical terms as well as nominalization are exploited. In addition, several texts have metaphorical words in them. This phenomenon influences the readability level of the texts. Furthermore, many clauses are constructed in complex arrangement, while some otheSrs incomplete in terms of grammar substances. This, therefore, add the negative quality of the texts. Several systemic strategies are provided to make the texts better. They can be effective models for the young writers as well as for the teachers of Bahasa Indonesia subject at elementary schools.Keywords: Genre, Cerita, Gramatika, Teks